Occupational Self-Selection: A Human Capital Approach to Sex Differences in Occupational Structure - Polachek, Solomon William (The Review of Economics and Statistics, 1981)
Solomon William Polachek, Occupational Self-Selection: A Human Capital Approach to Sex Differences in Occupational Structure, The Review of Economics and Statistics, Vol. 63, No. 1 (Feb., 1981), pp. 60-69